Bone Morphogenetic Protein-2 Induces Non-Canonical Inflammatory and Oxidative Pathways in Human Retinal Endothelial Cells - Al-Shabrawey, Mohamed; Hussein, Khaled; Wang, Fang; Wan, Ming; Elmasry, Khaled; Elsherbiny, Nehal; Saleh, Heba; Yu, Paul B.; Tawfik, Amany; Ibrahim, Ahmed S. (Frontiers in Immunology, 2021)
The mechanisms of diabetic retinopathy (DR), are not yet fully understood. We previously demonstrated an upregulation of retinal bone morphogenetic protein-2 (BMP2) in experimental diabetes and in retinas of diabetic human subjects. The purpose of current study was to investigate the role of non-canonical inflammatory pathway in BMP2-induced retinal endothelial cell (REC) barrier dysfunction. For this purpose, we used RT-PCR and western blotting to evaluate the levels of BMP2 signaling components (BMP2, BMP4, BMP receptors), VEGF, phosphorylated p38 MAPK and NFB, and oxidative stress markers in cultured human retinal endothelial cells (HRECs) subjected to BMP2 (50ng/ml) for up to 24 hours. Also, effect of high glucose (HG, 30mM D-glucose) on the expression of BMP2 and its downstream genes was examined in HRECs. H2-DCF is a fluorogenic dye that measures the levels of cellular reactive oxygen species (ROS) was used to measure the pro-oxidative effect of BMP2. Moreover, we evaluated the effect of inhibiting p38 and VEGF signaling on BMP2-induced HRECs barrier dysfunction by measuring the trans-endothelial cell electrical resistance (TER) using Electric Cell-substrate Impedance Sensing (ECIS). We also tested the effect of HG on the integrity of HRECs barrier in the presence or absence of inhibitors of BMP2 signaling. Our data reveals that BMP2 and high glucose upregulates BMP components of the BMP signaling pathway (SMAD effectors, BMP receptors and TGFligand itself) and induces phosphorylation of p38 MAPK and NFB with nuclear translocation of NFB. Inhibition of p38 or NFB attenuated BMP2-induced VEGF expression and barrier dysfunction in HRECs. Also, inhibition of VEGFR2 attenuated BMP2-induced barrier dysfunction. Moreover, BMP2 induces generation of ROS and endothelial nitric oxide synthase (eNOS) expression and activity in HRECs. Finally, HG upregulated BMP2 and its downstream genes (SMAD, BMP4, ALKs and TGF-) in HRECs and BMP2 inhibitors attenuated HG-induced HRECs barrier dysfunction. Our results suggest that in addition to the regular canonical SMAD signaling BMP2 induces non-canonical inflammatory pathway in HRECs via activation of p38/NFB pathway that causes the upregulation of VEGF and the disruption of HRECs. Inhibition of BMP2 signaling is a potential therapeutic intervention to preserve endothelial cell barrier function in DR.